THE EFFECTIVENESS OF THE ARABIC SPEECH PROGRAM AND ITS IMPACT ON IMPROVING STUDENTS' SPEAKING SKILLS AMONG EIGHTH-GRADE STUDENTS AT MINHAJ AL-HAQ ISLAMIC JUNIOR HIGH SCHOOL PURWAKARTA - Alimun Hakim; Saiful Islam; Kamarudin Kamarudin (Thariqah Ilmiah: Jurnal ilmu-ilmu kependidikan & Bahasa Arab, 2024)
This research aims to discover how the process of implementing the Arabic oratory program at Minhaj al-Haq Institute is and to discover the effect of this program in improving the speaking skill of students in the eighth semester. This research relied on the descriptive qualitative approach. The researcher obtained the results: The implementation of this program is arranged so that the institute allocates a special official for this program. The work of this official is to plan the program by: 1) creating the schedule and systems 2) distributing the official paper 3) setting the time. As for the students, they have the preparation: writing the text, listening and correcting it with the room professors, and memorizing the text. As for the effect of this program on speaking skills, the students in the eighth semester improve their language after starting this program due to their reading of books to research topics and the development of their courage in speaking Arabic in front of their fellow students as a result of their training and public speaking performance.